2024
DOI: 10.24084/repqj14.563
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Energy Transfer with Three-Phase Magnetic Field System: Experimental Results

Abstract: Abstract. In this paper a three-phase magnetic field system is applied to the wireless power transfer system. The research is directed not only to the distribution of the magnetic field but to optimize the energy transfer efficiency, and to reduce the electromagnetic field influence to the surroundings. The development of the future intelligent transportation system depends on the electric mobility, namely, the individual or the public electric vehicles. It is crucial to achieve progress in the batteries and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…10. The results confirmed that there were no packets with transmission errors, so it can be considered that the studied WPT system does not influence the data wireless channel operating at 2.4 GHz frequency in the case of Bluetooth applied as data channel [27,28].…”
Section: Experimental Partsupporting
confidence: 60%
“…10. The results confirmed that there were no packets with transmission errors, so it can be considered that the studied WPT system does not influence the data wireless channel operating at 2.4 GHz frequency in the case of Bluetooth applied as data channel [27,28].…”
Section: Experimental Partsupporting
confidence: 60%
“…But due to the usage of higher power transfer, it was hazardous to use. After a century, the concept of WET has gained importance in research again due to the low-power transfer (which is now not hazardous) and improvements of low power devices [77].…”
Section: Simultaneous Wireless Information and Power Transfer (Swipt)mentioning
confidence: 99%
“…The prototype was created by three coils connected in star and delta, separately, to form a three phase system supplied by 50 Hz frequency [31]- [33]. It appears that the behavior of the three phase magnetic induction measured on this prototype as base of WPT system.…”
Section: Experimental Partmentioning
confidence: 99%